Pathogenesis and immunobiology of brucellosis : review of brucella-host interactions - de Figueiredo, Paul; Ficht, Thomas A.; Rice-Ficht, Allison C.; Rossetti, Carlos Alberto; Adams, Leslie G. (Elsevier, 2022)
This review of Brucellaehost interactions and immunobiology discusses recent discoveries as the basis for pathogenesis-informed rationales to prevent or treat brucellosis. Brucella spp., as animal pathogens, cause human brucellosis, a zoonosis that results in worldwide economic losses, human morbidity, and poverty. Although Brucella spp. infect humans as an incidental host, 500,000 new human infections occur annually, and no patient-friendly treatments or approved human vaccines are reported. Brucellae display strong tissue tropism for lymphoreticular and reproductive systems with an intracellular lifestyle that limitsn exposure to innate and adaptive immune responses, sequesters the organism from the effects of antibiotics, and drives clinical disease manifestations and pathology. Stealthy brucellae exploit strategies to establish infection, including i) evasion of intracellular destruction by restricting fusion of type IV secretion systemdependent Brucella-containing vacuoles with lysosomal compartments, ii) inhibition of apoptosis of infected mononuclear cells, and iii) prevention of dendritic cell maturation, antigen presentation, and activation of naive T cells, pathogenesis lessons that may be informative for other intracellular pathogens. Data sets of next-generation sequences of Brucella and host time-series global expression fused with proteomics and metabolomics data from in vitro and in vivo experiments now inform interactive cellular pathways and gene regulatory networks enabling full-scale systems biology analysis. The newly identified effector proteins of Brucella may represent targets for improved, safer brucellosis vaccines and therapeutics.